Diagnostics of inflammaging in relation to sarcopenia - Barbara Morawin; Anna Tylutka; Filip Bielewicz; Agnieszka Zembron-Lacny (Frontiers Media S.A., 2023)
One of the theories about aging focuses on the immune response and relates to the activation of subclinical and chronic inflammation. This study was designed to investigate the relationship between inflammation and sarcopenia and to evaluate the influence of lifestyle on the inflammatory profile. Finally, therapeutic strategies to counteract the pathophysiological effect of skeletal muscle aging were also indicated. One hundred seventy-three individuals aged 71.5 ± 6.8 years were divided into two groups: sarcopenia and probable sarcopenia (n = 39) and no sarcopenia (n = 134). Sarcopenia was assessed according to the algorithm of the European Working Group on Sarcopenia in the older adults 2. C-reactive protein (CRP) (p = 0.011) and CRP/albumin ratio (p = 0.030) as well as IL-1β (p = 0.002), cfDNA (p < 0.001) and bilirubin levels (p = 0.002) were significantly higher in the sarcopenia group as opposed to the no sarcopenia group. No significant differences were observed between groups in the concentration of TNFα (p = 0.429) and IL-6 (p = 0.300). An inverse correlation was found between gait speed and cfDNA (rs = −0.234, p < 0.01) and IL-1β (rs = −0.263, p < 0.01). The ROC analysis of cfDNA, CRP, IL-1β and bilirubin ranged from 0.6 to 0.7, which confirms the association between sarcopenia and inflammatory mediators and indicates high clinical usefulness of cfDNA and bilirubin in sarcopenia prediction. We also indicated a link between inflammation and fitness level in the older adult thereby providing evidence that lifestyle exercise should be a key therapeutic strategy in sarcopenia prevention.